Habitat configuration matters when evaluating habitat-area effects on host–parasitoid interactions - With, Kimberly A.; Pavuk, Daniel M. (My University, 2019)
Higher trophic levels tend to be more sensitive to habitat fragmentation than lower trophic levels, which is why parasitism rates should decline in fragmented landscapes. Habitat loss and fragmentation (the subdivision of habitat) are typically interrelated processes, and thus, their effects are confounded in most studies. To address this, we quantified parasitism rates in pea aphids (Acyrthosiphon pisum) within an experimental model landscape system, in which we independently controlled the amount vs. the fragmentation of habitat (red clover, Trifolium pratense) within individual landscape plots (16 × 16 m). Aphid densities were generally unaffected by landscape pattern, except at the local scale for interior habitat cells within fragmented landscapes, which had significantly lower aphid densities than all other cell types. Aphid parasitism rates averaged about 40% and were significantly—albeit weakly—correlated with aphid density. Habitat amount had the greatest overall effect on parasitism rates, but fragmentation effects were evident in a shift in parasitism at intermediate habitat levels: Parasitism rates were higher in fragmented landscapes with <50% habitat, but higher in clumped landscapes with >50% habitat. Edge effects alone did not explain this shift in parasitism rates. Parasitism rates were uniformly high within edge habitat and fragmented landscapes, and thus, the shift in parasitism at intermediate habitat levels was driven by increasing parasitism rates within interior cells and clumped landscapes at higher habitat amounts. Habitat configuration is thus important for evaluating habitat-area effects on species interactions, as habitat amount only affected parasitism rates within less-fragmented landscapes in this system.
Citation: With, K. A., & Pavuk, D. M. (2019). Habitat configuration matters when evaluating habitat-area effects on host–parasitoid interactions. Ecosphere, 10(2), e02604. https://doi.org/10.1002/ecs2.2604
Keywords: Biological Control; Edge Effects; Insects; Parasitoids; Habitat Fragmentation; Aphids